Efficacy and safety profile of corticosteroids and non-steroidal anti-inflammatory drugs in COVID-19 management: A narrative review - Amponsah, Seth Kwabena; Tagoe, Benjamin; Adams, Ismaila; Bugyei, Kwasi Agyei (Frontiers in Pharmacology, 2022)
Due to the fact that coronavirus disease 2019 (COVID-19) is still prevalent, and in some parts of the world there appears to be an increase in incidence, it is relevant that health professionals and scientists know about recent or novel trends, especially drug treatments. Additionally, the safety profiles of these drug treatments need to be documented and shared with the public. Some studies have demonstrated the clinical benefits of non-steroidal anti-inflammatory drugs (NSAIDs) and corticosteroids in COVID-19 treatment. On the contrary, others have also reported that NSAIDs and corticosteroids may worsen symptoms associated with COVID-19. While some researchers have suggested that corticosteroids may be helpful if used in the early stages of COVID-19, there are still some conflicting findings regarding the use of corticosteroids in certain viral infections. Our review suggests that methylprednisolone, dexamethasone, and ibuprofen have therapeutic potential in reducing mortality due to COVID-19 among hospitalized patients. There is, however, scanty data that suggest that using NSAIDs increases the likelihood of getting COVID-19 infection or making the condition worse. In reality, evidence suggests that NSAIDs do not increase the risk of COVID-19 infections. Also, the literature reviewed suggests that corticosteroid treatment in COVID-19 was linked with a decrease in all-cause mortality and disease progression, but not an increase in adverse events when compared to no corticosteroid treatment.